W poszukiwaniu "nowej" teorii młodzieży. Uwagi wstępne = Towards a new theory of the youth - Zielińska, Maria (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author has undertaken a critical discussion with sociological theories in which the youth plays the key role. In Polish sociology there are currently many empirical studies which analyse various activity areas of young Poles, e.g., education, free time, life orientations, aspirations, life plans, relations with other generations, political activity (or rather lack of it), social activities, engagement in ecological movements, creative potential, critical potential or standard-setting abilities. A list of the topics covered is long. However, there is no deeper theoretical reflection. We are facing a deadlock in this regard.
Keywords: youth; theory; empirical studies; młodzież; teoria; badania empiryczne